Nasopharyngeal metatranscriptome profiles of infants with bronchiolitis and risk of childhood asthma: a multicentre prospective study. Issue 1 (14th July 2022) - Raita, Yoshihiko; Pérez-Losada, Marcos; Freishtat, Robert J.; Hahn, Andrea; Castro-Nallar, Eduardo; Ramos-Tapia, Ignacio; Stearrett, Nathaniel; Bochkov, Yury A.; Gern, James E.; Mansbach, Jonathan M.; Zhu, Zhaozhong; Camargo, Carlos A.; et al.
Background: Bronchiolitis is not only the leading cause of hospitalisation in US infants but also a major risk factor for asthma development. Growing evidence supports clinical heterogeneity within bronchiolitis. Our objectives were to identify metatranscriptome profiles of infant bronchiolitis, and to examine their relationship with the host transcriptome and subsequent asthma development. Methods: As part of a multicentre prospective cohort study of infants (age <1 year) hospitalised for bronchiolitis, we integrated virus and nasopharyngeal metatranscriptome (species-level taxonomy and function) data measured at hospitalisation. We applied network-based clustering approaches to identify metatranscriptome profiles. We then examined their association with the host transcriptome at hospitalisation and risk for developing asthma. Results: We identified five metatranscriptome profiles of bronchiolitis (n=244): profile A: virus RSV microbiome commensals ; profile B: virus RSV/RV-A microbiome H.influenzae ; profile C: virus RSV microbiome S.pneumoniae ; profile D: virus RSV microbiome M.nonliquefaciens ; and profile E: virus RSV/RV-C microbiome M.catarrhalis . Compared with profile A, profile B infants were characterised by a high proportion of eczema, Haemophilus influenzae abundance and enriched virulence related to antibiotic resistance. These profile B infants also had upregulated T-helper 17 and downregulated type I interferon pathways (false discovery rate (FDR) <0.005), and significantly higher risk for developing asthma (17.9% versus 38.9%; adjusted OR 2.81, 95% CI 1.11–7.26). Likewise, profile C infants were characterised by a high proportion of parental asthma, Streptococcus pneumoniae dominance, and enriched glycerolipid and glycerophospholipid metabolism of the microbiome. These profile C infants had an upregulated RAGE signalling pathway (FDR <0.005) and higher risk of asthma (17.9% versus 35.6%; adjusted OR 2.49, 95% CI 1.10–5.87). Conclusions: Metatranscriptome and clustering analysis identified biologically distinct metatranscriptome profiles that have differential risks of asthma. This study suggests a complex interplay between respiratory virus, airway microbiome and host immune response in infants with severe bronchiolitis, and their integrated contributions to the subsequent development of childhood asthma https://bit.ly/3xcM4ry